Research Note: Effect of exogenous enzyme supplementation on standardized ileal amino acid digestibility of guar korma meal in sexed broilers - Muhammad A Iqbal; Tanveer Ahmad; Muhammad S Ahmad; Usama Aftab; Nasir Mukhtar (Poultry Science, 2025)
Guar korma meal (GKM), a byproduct of the guar gum industry, has emerged as a potential alternative protein source in poultry nutrition, particularly the Indian subcontinent. This study aimed to investigate the standardized ileal digestibility (SID) of amino acids (AA) in GKM and assess the effects of two exogenous enzymes, mannanase and protease, on mitigating its antinutritional factors in male and female broilers. A total of 600 one-day-old broiler chicks (equally distributed between males and females) were assigned to eight dietary treatments plus two nitrogen-free diet groups for each sex, in a 2 × 2 × 2 factorial arrangement, sex (male and female) × dietary β-mannanase (0 and 500 gm/ton) × dietary protease (0 and 500 gm/ton). Each treatment had six replicate pens, with 10 sexed birds (single-sex) per pen. The experimental diet included GKM as the sole nitrogen source and a nitrogen-free diet for the determination of SID separately in male and female broilers. The predominant AAs in GKM were arginine, leucine, and isoleucine.. Male broilers exhibited (P < 0.05) higher digestibility than females for several AAs. Mannanase supplementation improved (P < 0.05) SID values of most determined AAs except for lysine, while protease improved (P < 0.05) the digestibility of all amino acids except arginine and lysine. These findings highlight GKM as a promising alternative protein source for broilers, with enzyme supplementation, particularly mannanase by enhancing amino acid digestibility, and notable differences observed between sexes that warrant consideration in diet formulation.